Agent Oriented Methodology for Crime Modelling and Simulation - Cheah, Wai Shiang; Sim, Yee Wai; Nurfauzabt, Binti Jalia; Muhammad Asyraf, Bin Khairuddin (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Agent-oriented methodology (AOM) is a comprehensive and unified agent methodology for agent-oriented software development. The potential of Agent Oriented Methodology has been revealed in domains like collaborative technology, video surveillance, and economics. However, it has not been explored in crime modelling and simulation. Although AOM is claimed to be able to cope with a complex system development, it is still not yet determined up to what extent this may be true. Therefore, it is vital to investigate to validate this methodology. This paper investigates the adoption of AOM in crime modeling and simulation. The novelty of this paper is to introduce a systematic way to model crime simulation. Through the AOM simulation, it is proven that the AOM can model the complex system in crime domain with various outcomes which supported a few existing research theories such as routine activity theory. AOM can provide a wider research platform which is useful for translating theories and micro-level behavior into models and simulation that can be studied, shared, tested and enhanced.